2005
DOI: 10.1143/jjap.44.765
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Properties of Delafossite-Type CuYO2 Doped with Calcium, Oxygen or Rare Earth Tb

Abstract: Delafossite-type CuYO2 and CuY1-x Ca x O2 (x≤0.05) samples exhibited a green-PL-emission band due to the Cu+ interconfiguration transition from 3d94s1 to 3d10 at room temperature. With increasing Ca concentration, the Cu+ emission shifted slightly to the shorter-wavelength side with a slightly weaker emission intensity. This slight change in Cu+ emission property is considered to be caused by the increase in hole concentration within the Cu+ layer arisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…1, the concentration quenching at the lower Tm concentration is also assumed to be related to the smaller distance between the Y 3+ sites in Table 1. Increase of p-type conductivity with increasing Ca concentration indicates doping with Ca 2+ acceptor cation on the Y 3+ site, causing hole concentration increases in co-doped CuR x Ca y Y 1-x-y O 2 samples, as reported previously in CuCa x Y 1-x O 2 samples [3,4,8,9]. The cause of the differences in the conductivity of CuR x Ca y Y 1-x-y O 2 samples with the same Ca concentration y is not yet clear.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…1, the concentration quenching at the lower Tm concentration is also assumed to be related to the smaller distance between the Y 3+ sites in Table 1. Increase of p-type conductivity with increasing Ca concentration indicates doping with Ca 2+ acceptor cation on the Y 3+ site, causing hole concentration increases in co-doped CuR x Ca y Y 1-x-y O 2 samples, as reported previously in CuCa x Y 1-x O 2 samples [3,4,8,9]. The cause of the differences in the conductivity of CuR x Ca y Y 1-x-y O 2 samples with the same Ca concentration y is not yet clear.…”
Section: Resultssupporting
confidence: 74%
“….08, y = 0.02~0.05), and that electrical conductivity of CuTb x Ca y Y 1-x-y O 2 were larger than that of CuTb x Y 1-x O 2 [9,10]. In addition, CuEu x Y 1-x O 2 (x ≤ 0.08) and CuEu x Ca y Y 1-x-y O 2 (x = 0.08, y = 0.02) have been tentatively prepared and characterized [10].…”
Section: Introductionmentioning
confidence: 92%
“…Electrical conductivities increase with the increase of temperature over the measured temperature range, indicating semiconducting behavior. It is reported that Ca-doping could enhance the electrical conductivity of CuYO 2 by introducing positive holes [19,21,[23][24][25]28]. In our experiment, the conductivities increase with the dopant concentration x when 0 ≤ x ≤ 0.06 and then decrease with x when 0.06 ≤ x ≤ 0.10, which may be ascribed to second phase formation.…”
Section: Resultssupporting
confidence: 51%
“…Delafossites ABO 2 can form either rhombohedral 3R (R3m) or hexagonal 2H (P6 3 /mmc) structures, depending on the stacking of the layers [18]. In the previous studies, the crystal structure, luminescence property and thermoelectric power of CuYO 2 were studied; its application to p-TCOs and hydrogen photocathode was explored [19][20][21][22]. Ca 2+ doped CuYO 2 has also been reported in the previous studies [23][24][25].…”
Section: Introductionmentioning
confidence: 92%
“…The first report on p-type TCO films of NiO was published in 1993 [5]. Delafossites such as CuScO 2 [6], CuFeO 2 [7], CuInO 2 [8], CuYO 2 [9], CuCoO 2 [10] have been widely studied since the discovery of p-type conductivity in transparent CuAlO 2 thin films in 1997 [11], which initiated extensive interest in this type of materials. Even though the electrical performance of these materials will never be able to compete with the well-established n-type TCOs such as Al-doped zinc oxide (AZO) or indium-tin oxide (ITO) due to their intrinsic low carrier mobility.…”
Section: Introductionmentioning
confidence: 99%